Ganoderma lucidum: Unutilized natural medicine and promising future solution to emerging diseases in Africa - Oke, M. A.; Afolabi, F. J.; Oyeleke, O. O.; Kilani, T. A.; Adeosun, A. R.; Olanbiwoninu, A. A.; Adebayo, E. A. (Frontiers in Pharmacology, 2022)
Ganoderma lucidum is a well-known medicinal mushroom that has been used for the prevention and treatment of different ailments to enhance longevity and health specifically in China, Japan, and Korea. It was known as “God’s herb” in ancient China as it was believed to prolong life, enhance the youthful spirit and sustain/preserve vitality. G. lucidum is seldom collected from nature and is substantially cultivated on wood logs and sawdust in plastic bags or bottles to meet the international market demand. Both in vitro and in vivo studies on the copious metabolic activities of G. lucidum have been carried out. Varied groups of chemical compounds including triterpenoids, polysaccharides, proteins, amino acids, nucleosides, alkaloids, steroids, lactones, lectins, fatty acids, and enzymes with potent pharmacological activities have been isolated from the mycelia and fruiting bodies of G. lucidum. Several researchers have reported the abundance and diversification of its biological actions triggered by these chemical compounds. Triterpenoids and polysaccharides of G. lucidum have been reported to possess cytotoxic, hepatoprotective, antihypertensive, hypocholesterolemic, antihistaminic effects, antioxidant, antimicrobial, anti-inflammatory, hypoglycemic antiallergic, neuroprotective, antitumor, immunomodulatory and antiangiogenic activities. Various formulations have been developed, patented, and utilized as nutraceuticals, cosmeceuticals, and pharmaceuticals from G. lucidum extracts and active compounds. Thus, this review presents current updates on emerging infectious diseases and highlights the scope, dynamics, and advances in infectious disease management with a particular focus on Ganoderma lucidum, an unutilized natural medicine as a promising future solution to emerging diseases in Africa.